Pengaruh Media Fermentasi Terhadap Produksi dan Karakterisasi Selulosa Bakteri Sari Pelepah Kelapa Sawit : Pengaruh Media Fermentasi Terhadap Produksi dan Karakterisasi Selulosa Bakteri Sari Pelepah Kelapa Sawit - Rahman, Arief Fazlul; Iffadhya Fathin, Adiba; Fachri Ibrahim, Nasution (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2026)
Fresh oil palm frond juice with mechanical pressing contains a concentration of easily fermented sugars such as glucose, sucrose, and fructose, suitable for use as a fermentation raw material because it does not inhibit microbial growth does not pose a risk to health and safety. The purpose of this study was to determine the effect of fermentation medium pH on bacterial cellulose from oil palm frond juice. Bacterial cellulose was produced using Acotobacter xilynum. Oil palm frond juice was prepared at 100 ml/g with the addition of protein with different pH media fermented for 8 days at room temperature in statistical conditions. The results of the thickness and weight of the best cellulose bacteria of pH 5 medium were 0.78 cm and 393,015 g/L. FE-SEM micrograph analysis for bacterial cellulose showed typical peaks found in cellulose with typical fibril threads. pH 3 had the lowest crystallinity value and the best crystallinity was at pH 5 based on FWHM. 1106 and 1423 cm-1 wave number is the C-O-C or C-O bond areas which are one of the bonds of the main chain of bacterial cellulose and the best tensile strength is the pH 5 treatment with a strength of 261.645 Mpa